Supply and Demand of Processed Potato Products in Kenya, Rwanda, and Uganda: Variety Requirements of Processing Companies and Implications for Trait Prioritization for Breeding - Naziri, D.; Devaux, A.; Hareau, G.; Wauters, P. (Springer, 2025)
The potato processing industry in Kenya, Rwanda, and Uganda is expanding rapidly. This study assesses the current situation and outlook of the local industrial potato processing sector and the alignment of the industry’s variety requirements with the priorities set by breeders. Currently, potato processing companies in the three countries use both varieties selected locally from public international germplasm and varieties introduced by Dutch seed companies, and their suitability for processing is discussed as well. Overall, the processing industry pays high attention to traits affecting processing efficiency and consumers’ acceptance while breeders, in spite of being aware of the characteristics required for processing varieties, are more focused on traits related to production and disease resistance. As the processing sector develops further, breeders will have to pay increased attention to the progressively stricter requirements of the industry, striking the right balance between farmers’ and processors’ variety requirements. While their opinions on the farmers’ acceptability of processing varieties diverge, breeders and industry agree about the challenges represented by the limited access to quality seed and poor business linkages between value chain actors in securing the supply of varieties suitable for processing. Based on these findings, it is recommended to pay more attention to both the development of dual-purpose varieties and the strengthening of the potato value chain through the improvement of business linkages between seed producers, farmers, and processing companies.